620 GASTRODUODENAL EOSINOPHILIA IS UNDER-APPRECIATED IN EOSINOPHILIC ESOPHAGITIS (EOE) PATIENTS WITH FUNCTIONAL BOWEL SYMPTOMS: A REAL LIFE EXPERIENCE. (17th September 2021) - Peterson, Kathryn; Genta, Robert; Rasmussen, Henrik; Youngblood, Bradford; Kamboj, Amol
Abstract: : Eosinophilic esophagitis (EoE) is currently thought to be the most common Eosinophilic Gastrointestinal Disorder. EoE patients often present with non-esophageal GI symptoms. Presence of EoE increases one's risk of developing distal eosinophilia, including eosinophilic gastritis (EG) and duodenitis (EoD). A diagnosis of EG/EoD often takes years due to lack of provider awareness and absence of consensus diagnostic guidelines. The aim was to evaluate the prevalence of EG/EoD in patients with EoE and functional abdominal symptoms. Methods: 52 EoE patients with extra-esophageal GI symptoms (i.e. abdominal pain, nausea, bloating, irritable bowel) who had stomach and small bowel biopsies interpreted as non-specific inflammation or normal were identified ('EoE + S'). 15 EoE patients without extra-esophageal complaints who had routine screening stomach and small bowel biopsies at their initial endoscopies were included as a control group ('EoE-S'). Biopsies taken at initial work up were identified and blocks were cut for H&E staining and assessment by an independent, blinded GI pathologist skilled in eosinophil (eos) assessment. Results: 45 EoE + S and 12 EoE-S patients were evaluated (Table 1). Common symptoms were abdominal pain, bloating and nausea. All prior pathology reports were consistent with non-specific inflammation or normal tissue. Upon blinded re-assessment, 8/45 (17.8%) EoE + S patients met criteria for EG (≥30 eos/hpf in ≥5 gastric hpfs). None of the EoE-S patients met criteria for EG. 24/45 (53%) EoE + S patients met criteria for EoD (≥30 eos/hpf in ≥3 duodenal hpfs). 7 patients had concomitant EG + EoD. 3/12 EoE-S patients met criteria for EoD. Peak gastric and duodenal eos counts for the EoE + S group were higher than for the EoE-S group. Conclusion: In patients with EoE and extra-esophageal GI complaints, review of gastric and duodenal biopsies previously reported as normal or 'non-specific inflammation' demonstrated a high discovery rate of gastroduodenal eosinophilia. These findings suggest that intentional evaluation of gastric and duodenal eos is indicated in patients with EoE and persistent non-esophageal GI symptoms. Increased awareness of EG/EoD and consensus diagnostic criteria may lead to the identification of currently undiagnosed patients with EG/EoD.